Diseño de Estrategias de Reactivación Económica Post Covid-19 del Sector Metalmecánico de la Ciudad de Duitama. (2022)
In Colombia, the arrival of COVID-19 forced thousands of people into confinement and the declaration of isolation as a preventive measure throughout the country, a situation that affected both the internal and external economy of the country, due to the fact that various economic activities were suspended and companies that had to be closed, generating great difficulties for this sector. In this context, the metal-mechanical sector of the city of Duitama was seriously affected by the closure of companies dedicated to this activity, because their work is carried out in person, making it impossible for workers to perform virtually, a strategy implemented by other companies and that for them represented in some cases an interesting innovation in labor matters. Taking into account the foregoing, the metal-mechanic sector, faced with the opening of the business sector, must have effective strategies that make way for economic reactivation, to mitigate the impact generated during the time that the isolation lasted and greater financial stability